2016
DOI: 10.3389/fimmu.2016.00175
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response of Amebiasis and Immune Evasion by Entamoeba histolytica

Abstract: Entamoeba histolytica is a protozoan parasite and the causative agent of amebiasis. It is estimated approximately 1% of humans are infected with E. histolytica, resulting in an estimate of 100,000 deaths annually. Clinical manifestations of amebic infection range widely from asymptomatic to severe symptoms, including dysentery and extra-intestinal abscesses. Like other infectious diseases, it is assumed that only ~20% of infected individuals develop symptoms, and genetic factors of both the parasite and humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 188 publications
(196 reference statements)
1
90
0
1
Order By: Relevance
“…EhCP5 is also associated with colon epithelial cell integrins and activates the NFkappaβ-mediated inflammatory response in host cells. Research in 2014 showed that EhCPA5 activates matrix metalloproteinase (MMP) by splitting (12,13) .…”
Section: Cysteine Proteases (Cp)mentioning
confidence: 99%
See 3 more Smart Citations
“…EhCP5 is also associated with colon epithelial cell integrins and activates the NFkappaβ-mediated inflammatory response in host cells. Research in 2014 showed that EhCPA5 activates matrix metalloproteinase (MMP) by splitting (12,13) .…”
Section: Cysteine Proteases (Cp)mentioning
confidence: 99%
“…Before adherence cells, trophozoites secrete immune modulators which stimulate epithelial cells to produce proinflammatory cytokine macrophage migration inhibitory factor (EhMIF). EhMIF induces inflammation resulting in increased production of matrix metalloproteinase (MMP) (13) .…”
Section: Figure 2 Sequential Model Of Cell Killing Andmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of excellent reviews have recently been published on the immune response to Entamoeba 18 , immune evasion mechanisms by the parasite 19 , trogocytosis (nibbling of host cells by the amoeba) 2022 , and virulence determinants 23 . Thus, we will focus on topics for which recent reviews are not available.…”
Section: Introductionmentioning
confidence: 99%